Stategi Dakwah Konselor Dalam Peningkatan Religiusitas - Khoiroh, Anikmatul (Institut Agama Islam Syarifuddin Lumajang, 2025)
The era of modernity shows that increasingly advanced human civilization has resulted in an increasingly complex lifestyle. The effects of modernization experienced by humans today result in them not having enough time to reflect on their own existence so that each individual is easily tired both physically and mentally which will gradually lead to mental disorders This study attempts to review the literature that explains the efforts of a counselor in directing someone who is experiencing moral problems to return to the teachings of their respective religions; and describes the impact of activities from religious relationships on behavioral changes. The results of this study indicate that Counseling Da'wah A wise effort is to present a da'wah model through guidance and counseling, namely the spread of Islamic teachings that are very specific among certain targets. It displays personal relationships and is more oriented towards solving individual problems experienced, The conclusion of this study confirms that the application of religious values ​​in the Counseling process as a form of da'wah can be done by developing a religious character formulated into the objectives of religious counseling services.